Lipoinjection with Adipose Stem Cells for Nasal Modeling: Rhino Cell, a Highly Versatile Alternative - Castro-Govea, Yanko; García-Garza, Jorge A.; Vázquez-Lara, Sergio E.; González-Cantú, Cynthia M.; Chacón-Moreno, Hernán; Cervantes-Kardasch, Víctor H. (Archives of Plastic Surgery, 2023)
It is undeniable that a significant number of patients who want to improve their facial appearance is increasingly interested in nonsurgical procedures. Without a doubt, the use of autologous fat could not be left out as a magnificent alternative for nasal modeling simply because of four influential factors: ease of collection, compatibility, the temporality of the results, and safety. This work describes an innovative alternative technique for nasal modeling using micrografts enriched with adipose-derived mesenchymal stem cells (ASCs). With this technique, fat was collected and divided into two samples, nanofat and microfat. Nanofat was used to isolate the ASCs; microfat was enriched with ASCs and used for nasal modeling. Lipoinjection was performed in a supraperiosteal plane on the nasal dorsum. Through a retrolabial access, the nasal tip and base of the columella were lipoinjected. We consider that nonsurgical nasal modeling using micrografts enriched with ASCs can be an attractive and innovative alternative. This technique will never be a substitute for surgical rhinoplasty. It can be performed in a minor procedure area with rapid recovery and return to the patient's daily activities the next day. If necessary, the procedure can be repeated.
Keywords: nonsurgical rhinoplasty; nasal modeling; ASCs; nasal lipoinjection; nanofat